Rainhas do rádio e rainhas do lar: representações femininas na era do rádio - Freitas, Jaqueline Maria (2013)
The invention of the radio also led to the invention of the listener. And the endless transformations started with the new media would change the face of the first five decades of the twentieth century in a definitive way, especially if we talk about women´s everyday. As listeners or artists, women imprinted their mark to the radio. The "queens of home" elected their favorites, and, the "queens of radio", were in the end the "vassals" of the first ones, since they represented their alter ego. Generally speaking, poor girls who conquered stardom and were raised to the status of nobility, representing what housewives would like to be but couldn´t. This work will attempt to portray this relationship, using real (the personal story of the queens of radio and radio actresses) and fictitious figures (the Leniza Maier´s character of A Estrela Sobe [The Star Rises]), in an attempt to understand these women who, with the power of the waves, were authors of story, and how their efforts contributed to the construction of female identities in their time.